2002 IEEE International Conference on Industrial Technology, 2002. IEEE ICIT '02.
DOI: 10.1109/icit.2002.1189305
|View full text |Cite
|
Sign up to set email alerts
|

Certain control strategies for three-phase semi-converters for the operation of self-excited induction generators

Abstract: The application of certain firing angle control techniques such as Negative Firing Angle Control, Extinction Angle Control, and Symmetrical Angle Control has been studied for the first time, for the operation of three-phase semi-converters. The input and output voltage and current waveforms and the expressions for the performance quantities 01' the converter, in terms of the respective control angles a, p, and y, have been analytically derived. These results have been confirmed in the simulation of the convert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…With varying wind speeds, these generators produce variable voltage-variable frequency power output and so some form of power converter is required for obtaining a desired constant dc voltage. Usually, in the analysis of three-phase or single-phase ac to dc converters, a sufficiently large inductance in series with the load is assumed, which results in a constant and continuous dc load current with negligible ripple content [1][2][3][4]. In case, this inductance is not large enough, the current will cease to be constant and different current patterns would occur.…”
Section: List Of Symbolsmentioning
confidence: 98%
“…With varying wind speeds, these generators produce variable voltage-variable frequency power output and so some form of power converter is required for obtaining a desired constant dc voltage. Usually, in the analysis of three-phase or single-phase ac to dc converters, a sufficiently large inductance in series with the load is assumed, which results in a constant and continuous dc load current with negligible ripple content [1][2][3][4]. In case, this inductance is not large enough, the current will cease to be constant and different current patterns would occur.…”
Section: List Of Symbolsmentioning
confidence: 98%
“…Certain firing angle control schemes other than the conventional phase angle control (PAC), namely, Negative Firing Angle Control (NFAC), Extinction Angle Control (EAC) and Symmetrical Angle Control (SAC) have been adopted for the semi-converter [12,13].The need for each of these control schemes to accommodate a wide variation in wind speed, has also been brought out with an example. The relevant analytical expressions have been derived for the design of such systems.…”
Section: Introductionmentioning
confidence: 98%
“…With the advent of self-commutating devices such as power MOSFETs and IGBTs, a single stage controlled rectifier circuit has been proposed by few authors, eliminating the forced commutating capacitors. Further, it has also been shown that, in maintaining the desired constant voltage at the dc terminals of the rectifier, different control strategies such as symmetrical angle control, extinction angle control and negative firing angle control could be adopted with such power converters, to suit the different ranges of the varying rotor speed [16][17][18] in the wind driven applications.…”
Section: Introductionmentioning
confidence: 99%